2017
DOI: 10.1002/chem.201702621
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Noninnocence in Iron Corroles: Insights from Optical and X‐ray Absorption Spectroscopies and Electrochemical Redox Potentials

Abstract: Two new series of iron meso-tris(para-X-phenyl)-corrole (TpXPC) complexes, Fe[TpXPC]Ph and Fe[TpXPC]Tol, in which X=CF3, H, Me, and OMe, and Tol=p-methylphenyl (p-tolyl), have been synthesized, allowing a multitechnique electronic–structural comparison with the corresponding FeCl, FeNO, and Fe2(μ-O) TpXPC derivatives. Optical spectroscopy revealed that the Soret maxima of the FePh and FeTol series are insensitive to the phenyl para substituent, consistent with the presumed innocence of the corrole ligand in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 49 publications
(62 reference statements)
6
66
0
Order By: Relevance
“…Recently, Nocera and Kar independently reported that several copper complexes of meso ‐aryl‐substituted corroles consist of the central copper(II) ion and the divalent corrole π‐radical ligand with strong antiferromagnetic interaction between the copper(II) and the π‐radical fragment, thereby behaving as an overall singlet spin‐state even at room temperature. Similar ligand non‐innocent behaviors have also been known for silver octabromocorroles, chloroiron and nitrosoiron corroles, triphenylphosphine cobalt corroles, and chloromanganese corroles . Another important observation is the metal‐ligand interaction depending on the size of the ligand.…”
Section: Introductionsupporting
confidence: 58%
“…Recently, Nocera and Kar independently reported that several copper complexes of meso ‐aryl‐substituted corroles consist of the central copper(II) ion and the divalent corrole π‐radical ligand with strong antiferromagnetic interaction between the copper(II) and the π‐radical fragment, thereby behaving as an overall singlet spin‐state even at room temperature. Similar ligand non‐innocent behaviors have also been known for silver octabromocorroles, chloroiron and nitrosoiron corroles, triphenylphosphine cobalt corroles, and chloromanganese corroles . Another important observation is the metal‐ligand interaction depending on the size of the ligand.…”
Section: Introductionsupporting
confidence: 58%
“…The Mo(4d z 2)-corrole("a 2u ") interaction evident in the HOMO−2 and LUMO (Fig. 5) is, topologically, exceedingly similar to analogous interactions involving the 3d z 2 orbital in MnCl, 23 FeCl, [10][11][12][13][14][15] FeNO, 27 and Co-PPh 3 31 corroles. Importantly, this picture was fully borne out by an examination of the 4d-based natural bond orbitals (NBOs) of the molecule.…”
Section: Dalton Transactions Papermentioning
confidence: 70%
“…[6][7][8] The rarity of well-characterized, noninnocent 4d and 5d metal systems reflects in part the rarity of stable, paramagnetic complexes involving these elements (which in turn reflects their preference for low-spin states), robbing magnetic resonance methods such as paramagnetic NMR and EPR spectroscopy of the ability to characterize the phenomenon by probing molecular spin densities. [9][10][11][12][13][14][15][16] It is against this backdrop that we have chosen to reexamine paramagnetic molybdenum- 17 and tungsten- 18 dichlorido "Viking-helmet" corroles with density functional theory methods for possible signs of a noninnocent corrole (Scheme 1; see also Notes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sterically hindered TMP ligands was chosen to improve the stability of the Cr(IV) complex, but the differences in peripheral transition metal d electron counts, XAS has only been infrequently applied to Cr porphyrins and indeed to metalloporphyrin-type complexes in general, except for those involving Mn and Fe. [1][2][3][4][5][6][7][8] Indeed, only one directly relevant study has been reported in the literature, focusing on Cr IV [TTP]O and Cr V [TTP]N, where TTP 2À is the dianion of meso-tetra(p-tolyl) porphyrin. 9 Understandably, we have used substantially improved theoretical methods in the present study to model the Cr K-edge XAS data on the high-valent compounds 2 and 3, and where appropriate, we will point out similarities and differences relative to the earlier study.…”
Section: Introductionmentioning
confidence: 99%